2020
DOI: 10.1080/15476286.2020.1736868
|View full text |Cite
|
Sign up to set email alerts
|

GR-mediated FTO transactivation induces lipid accumulation in hepatocytes via demethylation of m6A on lipogenic mRNAs

Abstract: Chronic stress or excessive exposure to glucocorticoids (GC) contributes to the pathogenesis of non-alcoholic fatty liver disease (NAFLD). Glucocorticoid receptor (GR) mediates the action of GC, but its downstream signalling is not fully understood. Fat mass and obesity associated (FTO) protein and its demethylation substrate N6-methyladenosine (m 6 A) are both reported to participate in the regulation of lipid metabolism, yet it remains unknown whether they are involved in GC-induced hepatic lipid accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 49 publications
3
49
0
Order By: Relevance
“…90,91 More importantly, FTO knockdown using shRNA significantly alleviated dexamethasone-induced fatty liver in mice. 92 Taken together, these findings suggest that FTO may play a deleterious role in hepatocytes under lipotoxic conditions by altering m 6 A modifications (Fig. 3).…”
Section: Lipid Metabolism Nafld and Nashmentioning
confidence: 75%
See 1 more Smart Citation
“…90,91 More importantly, FTO knockdown using shRNA significantly alleviated dexamethasone-induced fatty liver in mice. 92 Taken together, these findings suggest that FTO may play a deleterious role in hepatocytes under lipotoxic conditions by altering m 6 A modifications (Fig. 3).…”
Section: Lipid Metabolism Nafld and Nashmentioning
confidence: 75%
“…151 A recent study has demonstrated that MA can prevent oleic acid/dexamethasone-induced increases in total triglycerides in primary hepatocytes. 92 In addition, some natural products targeting RNA methylation have also been reported to have hepatoprotective effects. For instance, the methyl donor betaine can alleviate NAFLD in mice in an FTO-dependent manner, 152 while the yellow polyphenolic pigment curcumin has been shown to attenuate LPS-induced liver injury and liver lipid metabolism disorder by increasing m 6 A RNA methylation 153 ; however, further studies are required to investigate the side effects of these natural products.…”
Section: Therapeutic Potential Of Targeting M 6 a Regulatorsmentioning
confidence: 99%
“… 107 FTO knockdown significantly mitigates dexamethasone-induced fatty liver (a mouse model of NAFLD). 108 Moreover, it is reported that exenatide therapy ameliorates lipid accumulation and inflammatory changes in NAFLD by decreasing FTO expression in a PI3K-dependent mechanism. 109 …”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…In the present study, the mechanisms underlying stress resilience-coupled FTO expression in the VTA remains unknown. Considering that dopamine neurons in the VTA are sensitive to stress, which mediates stress susceptibility and resilience, and a recent study ( Hu et al, 2020 ) has reported that glucocorticoid receptor-dependent FTO transactivation induces lipid accumulation in hepatocytes, we hypothesized that a glucocorticoid-regulated FTO expression in the VTA may contribute to stress resilience. Further investigation is required.…”
Section: Discussionmentioning
confidence: 99%